The Principle of Implicit Ignorance - Curtsmith, Phillip (Stance: an international undergraduate philosophy journal, 2012)
The following is a foundationalist exercise based upon a single observation or postulate distinguishing one’s knowledge of information versus one’s knowledge of one’s former unknowing of that information. This postulate is titled the “principle of implicit ignorance.” Utilizing this postulate, several theorems are constructed including the equivalence to Hume’s thesis regarding the absence of knowledge of a necessary connection. The postulate is then negated, demonstrating equivalence to Kant’s thesis regarding the presence of synthetic a priori statements. The final result is a single general epistemic postulate that brokers between the two respective positions. Because both systems are the result of this general principle, rejecting the results of one system necessarily forces one into the contrary position.